2016
DOI: 10.1159/000444586
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Polybrominated Diphenyl Ethers in Girls with Premature Thelarche

Abstract: Background/Aims: Polybrominated diphenyl ethers (PBDEs) are widely used as flame retardants and have shown endocrine disruption properties in experimental studies. The aim of this study was to investigate the association between the exposure to PBDEs and alterations of puberty in girls referred for idiopathic central precocious puberty (ICPP) and premature thelarche (PT). Methods: A case-control study was conducted in 124 girls: 37 girls with ICPP (mean age 7.4 ± 0.9 years), 56 with PT (mean age 5.7 ± 2.1 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Some of the possible causes of premature thelarche include increased FSH (but not LH) secretion, excessive dietary intake of estrogens such as phytoestrogens and increased breast sensitivity to circulating estrogens (62), obesity and the role of endocrine-disrupting chemicals (EDCs) such as polybrominated diphenyl ethers (PBDEs), which can cause premature thelarche when it reaches high serum concentrations (63). Crofton et al tried to test whether premature thelarche is associated with increased FSH-driven follicular development; they measured inhibin B (whose role is stimulating estradiol synthesis) and FSH in girls with premature thelarche, central precocious puberty and normal pubertal controls matched for ages and they found that patients with precocious thelarche had inhibin B and FSH levels much higher than their age-matched controls and similar to the levels found in girls with precocious puberty, providing evidence that precocious thelarche is associated with increased follicular development (64).…”
Section: Premature Thelarchementioning
confidence: 99%
“…Some of the possible causes of premature thelarche include increased FSH (but not LH) secretion, excessive dietary intake of estrogens such as phytoestrogens and increased breast sensitivity to circulating estrogens (62), obesity and the role of endocrine-disrupting chemicals (EDCs) such as polybrominated diphenyl ethers (PBDEs), which can cause premature thelarche when it reaches high serum concentrations (63). Crofton et al tried to test whether premature thelarche is associated with increased FSH-driven follicular development; they measured inhibin B (whose role is stimulating estradiol synthesis) and FSH in girls with premature thelarche, central precocious puberty and normal pubertal controls matched for ages and they found that patients with precocious thelarche had inhibin B and FSH levels much higher than their age-matched controls and similar to the levels found in girls with precocious puberty, providing evidence that precocious thelarche is associated with increased follicular development (64).…”
Section: Premature Thelarchementioning
confidence: 99%
“…To date, there have been limited studies on pubertal timing, with inconsistent results that depend on the timing of exposure (Table 3) [76,87,90-93]. The limited studies have shown positive associations with premature thelarche [92], earlier pubertal development [90], and age at menarche [91], although associations with later onset of puberty [76,93] or no association [87] have also been reported. Three prospective studies have reported contrasting outcomes in which prenatal PBB/PBDE exposures showed no association [87] or associations with both earlier [90] and later [93] pubertal timing.…”
Section: Polybrominated Flame Retardantsmentioning
confidence: 99%
“…However, the upper quartile values were comparable to the serum concentrations and was significantly associated with an increased risk of earlier menarche [ 233 ]. In the second study, a case-control study including 37 girls with idiopathic central precocious puberty and 56 with premature thelarche PBDE serum concentrations corrected for total lipid content resulted significantly higher in girls with premature thelarche than in controls and higher than in idiopathic central precocious puberty girls [ 236 ]. The effect of in utero exposure to PBDEs on sexual maturation was evaluated in Michigan girls whose mothers were accidentally exposed through diet to these compounds.…”
Section: Effects Of Edcs On Pubertymentioning
confidence: 99%